2018
DOI: 10.11158/saa.23.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of chlorfenapyr on the life table parameters of two-spotted spider mite, Tetranychus urticae (Acari: Tetranychidae)

Abstract: The two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) is a well-known pest mite with an extensive host range worldwide. The control of T. urticae populations mostly relies on the application of synthetic acaricides or pesticides. Chlorfenapyr is a broad spectrum insecticide/miticide effective against agriculturally important pests. In this study, sublethal effects (LC10, LC20 and LC30) of this insecticide on demographic parameters of T. urticae based on the age-stage, two-sex life table … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
5
11
0
Order By: Relevance
“…In the current study, the population parameters and offspring of TSSM female adults treated with sublethal concentrations of fluralaner were investigated and to our knowledge, this is the first report of the sublethal effects of fluralaner on mites. Referring to other published data 4,27,28,46 (Table S2) After TSSM eggs were treated with LC 30 of fluralaner, egg duration was increased by 15.50% (Table 3), which was in agreement with report by Wang et al 28 However, the duration, fecundity and longevity of female adults in the LC 30 treatment were significantly decreased by 35.04%, 28.42%, and 13.21%, respectively, compared with the control treatment. Meanwhile, we found that sublethal concentrations of spinetoram (LC 20 ) and bifenthrin (LC 25 ) could reduce the duration of female adults, 4,28 and sublethal concentrations of diflovidazin (LC 20 ) and chlorfenapyr (LC 30 ) could reduce longevity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, the population parameters and offspring of TSSM female adults treated with sublethal concentrations of fluralaner were investigated and to our knowledge, this is the first report of the sublethal effects of fluralaner on mites. Referring to other published data 4,27,28,46 (Table S2) After TSSM eggs were treated with LC 30 of fluralaner, egg duration was increased by 15.50% (Table 3), which was in agreement with report by Wang et al 28 However, the duration, fecundity and longevity of female adults in the LC 30 treatment were significantly decreased by 35.04%, 28.42%, and 13.21%, respectively, compared with the control treatment. Meanwhile, we found that sublethal concentrations of spinetoram (LC 20 ) and bifenthrin (LC 25 ) could reduce the duration of female adults, 4,28 and sublethal concentrations of diflovidazin (LC 20 ) and chlorfenapyr (LC 30 ) could reduce longevity.…”
Section: Discussionsupporting
confidence: 90%
“…According to the results shown in Table , the net reproduction rate ( R 0 ), intrinsic rate of increase ( r ) and finite rate of increase ( λ ) were decreased significantly in sublethal treatments compared with control, which were in line with previous reports on bifenthrin, chlorfenapyr, diflovidazin and fenazaquin, but completely contrary to spinetoram . Hence, we speculate that a sublethal concentration of fluralaner had virulent effects on offspring and led to a population decrease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It is fundamental to clarify effects of acaricide sublethal doses on mite population dynamics . We hypothesized that, when exposed to spirodiclofen sublethal doses, B. yothersi undergoes changes of certain biological parameters and hence its population increases faster.…”
Section: Introductionmentioning
confidence: 99%